ANALYSIS OF SURFACE ELECTROMYOGRAPHY OF THE QUADRICEPS MUSCLE DURING LUNGE MOVEMENTS IN THE SPORT OF FENCING WITH A HISTORY OF KNEE AND QUADRICEPS CORNER PAIN (Q-ANGLE) - Adhy Kurniawan; Teguh Santosa; Nuruddin Priya Budi Santoso, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2023)
Data collection techniques in this study were obtained using surface electromyography records. Treatment for 1 meeting. Data analysis used a Nonparametric Test in the form of a Two Independent Samples Test with the Mann Whitney U Test type. The research results obtained were 1) Differences in activation of the rectus femoris muscle for pain had a p-value of 0.034, 2) Differences in activation of the vastus medialis muscle for pain had a p-value of 0.289, 3) Differences in activation of the vastus lateralis muscle had a p-value of 0.034, 4) The difference in activation of the rectus femoris muscle to the q-angle has a p value of 0.077, 5) The difference in activation of the vastus medialis muscle to the q-angle has a p value of 1.000 and 6) The difference in activation of the vastus lateralis muscle to the q-angle has a p value of 0.289. The conclusions of this study are as follows 1) There is a difference in activation of the rectus femoris muscle for fencers who experience pain, 2) There is no difference in activation of the vastus medialis muscle for fencers who experience pain, 3) There is a difference in activation of the vastus lateralis muscle for fencers who experience pain pain, 4) There was no difference in activation of the rectus femoris muscle against the q-angle, 5) There was no difference in activation of the vastus medialis muscle against the q-angle, and 6) There was no difference in activation of the vastus lateralis muscle against the q-angle.